Hukuman Cambuk: Pandangan Ulama Kontemporer, Penerapan, Serta Korelasi dengan HAM - Nur Aliah Mufidah; Ananda Putri; Muh. Alief Ramadhan; Kurniati Kurniati (Ethics and Law Journal: Business and Notary, 2024)
Aceh is the only province in Indonesia that applies Islamic law, including Islamic criminal law with caning. The presence of Aceh with Islamic law in a secular country like Indonesia is an interesting phenomenon to be studied further. This research aims to provide a deeper understanding to the public regarding caning in Aceh, so that there are no misunderstandings in its interpretation. In this research, the method used is an Islamic legal approach with a normative juridical focus. The author analyzes cases of caning in Indonesia, linking them to the principles of Human Rights using data sources from the Koran, laws, journals and online media. The results of this research show that there is support from the Ulama Consultative Council and the Islamic Sharia Service Agency for the implementation of caning in Aceh. The reason is because caning is considered to originate from the aspirations of the community. Implementation according to procedures in Governor's Regulation Number 10 of 2005, shows compliance and is not arbitrary, is considered to be in accordance with the principles of justice and does not violate human rights, because the process of carrying out caning punishment really pays attention to the principles of justice and applicable regulations. Thus it can be concluded that Contemporary ulama support the existence of caning punishment in Aceh on the grounds that the application of this caning punishment will create a deterrent effect, not because of physical factors but because of psychological factors. Meanwhile there are ulama who do not support caning punishment, but it is not published because it is covered by many ulama who supports the caning punishment. Meanwhile, the implementation of caning punishment in Aceh is regulated so that it does not physically torture the convict, because caning punishment has more of an impact on psychological factors. This caning punishment also does not conflict with human rights because its implementation prioritizes aspects of justice in it. The novelty of this research is that it discusses the views of contemporary ulama and analyzes the correlation between caning punishment and human rights.